2012
DOI: 10.3201/eid1812.120061
|View full text |Cite
|
Sign up to set email alerts
|

Arctic-like Rabies Virus, Bangladesh

Abstract: Arctic/Arctic-like rabies virus group 2 spread into Bangladesh ≈32 years ago. Because rabies is endemic to and a major public health problem in this country, we characterized this virus group. Its glycoprotein has 3 potential N-glycosylation sites that affect viral pathogenesis. Diversity of rabies virus might have public health implications in Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 14 publications
4
20
0
Order By: Relevance
“…Our phylogenetic analyses were in agreement with previous studies [ 7 , 11 , 22 , 25 ] and revealed that rabies viruses from Thailand, Malaysia, Cambodia, Laos and Vietnam had originated from a common ancestor. The lineages circulating in Laos are closely related but are not same as in other SEA countries, which are indicating that invasion of rabies viruses in Laos from these countries possibly did not occur recently.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our phylogenetic analyses were in agreement with previous studies [ 7 , 11 , 22 , 25 ] and revealed that rabies viruses from Thailand, Malaysia, Cambodia, Laos and Vietnam had originated from a common ancestor. The lineages circulating in Laos are closely related but are not same as in other SEA countries, which are indicating that invasion of rabies viruses in Laos from these countries possibly did not occur recently.…”
Section: Discussionsupporting
confidence: 92%
“…This is not unusual, co-circulation of two types of canine rabies virus has been documented in countries of Africa [ 4 , 20 ], six lineages in China [ 21 , 22 ] and Romania [ 23 ], and up to 30 different lineages of bat rabies virus in the United States [ 24 ]. In smaller countries possibly circulation of one lineage of rabies virus is usual [ 17 , 25 ]. Considering the size of the country and movement of people and dogs to and from the rabies endemic countries, it is likely that that multiple lineages will co-circulate in Laos.…”
Section: Discussionmentioning
confidence: 99%
“…Although RABV belonging to the Arctic-like sub-clade was already known to circulate in Nepal [5] , [35] , this study has identified for the first time the presence of two Arctic-like sub-clades of RABV (AL-1 and AL-3) in this country. Within the AL-1 sub-clade, we identified two Nepalese isolates belonging to the AL-1a lineage, which encompassed virus strains from India but also probably from Bangladesh and Bhutan, although for the latter phylogenetic information contained in only partial N gene sequences available in public databases was not informative enough to classify strains into either AL-1a or AL-1b lineages (data not shown) [36] , [37] . AL-1a viruses have been present in India, which forms the largest immediate border with Nepal, since at least 1988 and represent currently the main phylogroup of RABV circulating in the country [26] , [38] ( Figures 1 , 2 and S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chiou et al [5] found 97-99% nucleotide identity of the N gene of rabies virus within three isolates from Taiwan Ferret Badgers. Jamil et al [8] revealed 98-100% nucleotide identity between N gene sequences of rabies virus from seven brain samples. Reddy et al [18] found 88.8-99.7% homology of nucleoprotein gene between 30 Indian rabies isolates and the standard Pasteur virus strain.…”
Section: Discussionmentioning
confidence: 99%